Technical Efficiency in Bitter Melon Plants Using Data Envelopment Analysis (DEA) Model in Tanah Laut District - Rana Pertiwi Pohan; Yudi Ferrianta; Nuri Dewi Yanti (International Journal of Science and Environment (IJSE), 2024)
Farm technical efficiency involves maximizing output while minimizing input costs. In Tanah Laut Regency, bitter melon production fluctuates annually due to climatic factors and inefficient input use. On average, farmers use 0.47 hectares of land, 166 grams/ha of seeds, 2,659 kg/ha of organic fertilizer, 208 kg/ha of inorganic fertilizer, 7.08 liters/ha of liquid pesticides, 7.24 kg/ha of solid pesticides, and 339 HKSP of labor. Data Envelopment Analysis (DEA) indicates that farmers are technically inefficient, with average technical efficiencies of 80.8% (CRS-DEA), 89.9% (VRS-DEA), and 89.8% (SE-DEA). Among the farmers, 32% operate under increasing returns to scale (IRS), 26% under constant returns to scale (CRS), and 42% under decreasing returns to scale (DRS). A logit regression model reveals that education level, farming experience, and number of family members significantly impact technical efficiency, while age, land ownership status, and off-farm income do not. To enhance efficiency, farmers should reduce input use by emulating the practices of their more efficient peers.